Midnight at the haunted hotel - Lee, J. M. (Joseph M.); Warner, Gertrude Chandler, 1890-1979 (Boxcar children interactive mystery., 2018)
The Boxcar Children are investigating strange events at a hotel that some people say is haunted, and it seems like every room holds a new surprise. In this interactive, choose-your-path mystery, readers will put their sleuthing skills to the test, making decisions that will either help the Aldens crack the case or lead them deeper into the haunted hotel.